New Philanthropy and Social Justice : Debating the Conceptual and Policy Discourse - Morvaridi, Behrooz (Book collections on Project MUSE., 2015)
Explores the politics and ideology behind a new form of philanthropy whereby wealthy capitalists and private corporations establish initiatives to reduce poverty, disease and food security. Is this new philanthropy just a sticking plaster without long-term results as it fails to tackle inequality?